Second Thoughts on Capital-Intensity of Investment - Dobb, Maurice (Review of Economic Studies, 1956)
Journal Article Second Thoughts on Capital-Intensity of Investment Get access Maurice Dobb Maurice Dobb Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 1, 1956, Pages 33–42, https://doi.org/10.2307/2296234 Published: 01 July 1956